Editorial - Gautam, Ganga Ram (Janabhawana Research Journal, 2025)
It is with great academic pride that we present Volume 4, Issue 1 of the Janabhawana Research Journal, published by the Research Management Cell (RMC) of Jana Bhawana Campus, Godawari-11, Lalitpur. This issue features fourteen peer reviewed scholarly articles from the areas of economics, education, culture, literature, environment, governance, and human resource development, highlighting the journal’s commitment to interdisciplinary excellence. The issue begins with an empirical analysis on operating efficiency and semi-strong market efficiency of Nepalese commercial banks by Shrestha, Bedari, and Pant. Their use of Data Envelopment Analysis (DEA) and dynamic panel modeling reveals that bank stock prices in Nepal are not semi-strong efficient, indicating that public information is not adequately reflected in market prices. In the field of education, Chhetri and Joshi examine the epistemological beliefs and teaching efficacy among secondary mathematics teachers in Gandaki Province. Statistical analysis indicates a significant relationship between belief systems, demographics, and teaching effectiveness, offering important implications for teacher development. On the cultural front, Khadka, Bhattarai, and Thakur explore the multidimensional nature of the Chhath festival. Their qualitative study interprets the festival through cultural diffusion theory and presents it as a rich blend of spiritual, economic, scientific, and social significance in Nepal’s Terai region and beyond. Milan Shrestha’s article on the federal system in Nepal provides a timely reflection on the constitutional and legal frameworks guiding federalism. The study highlights the gaps in institutional capacity and autonomy that must be addressed to ensure effective decentralization and equitable governance. Dhungel and Paudel apply trauma theory to Sylvia Plath’s Ariel, analyzing how poetic devices represent suffering, resilience, and fragmented memory. Their interpretation affirms the cathartic and rhetorical power of literature in expressing psychological trauma. As socio-literary critique, Narendra Koirala examines class power relations in Narayan Dhakal’s Irfan Ali. Drawing from Gramsci and Foucault, the article highlights how oppressive structures persist through the discursive machinery of the Panchayat regime, leaving the subjugated class voiceless and powerless. Timalsina and Katwal investigate the challenges of higher education students balancing work and study in Godawari Municipality. Financial burdens, lack of academic flexibility, and mental stress are the prominent issues, calling for more inclusive educational support systems. Sedunath Dhakal offers a comparative literary analysis of power and resistance in Orwell’s Shooting an Elephant and Erdrich’s Snares. He shows how marginalized groups express resistance in varied forms, symbolic or overt, depending on social contexts and historical moments. The economic viability of animal husbandry is the focus of Basnet and Bista’s cost-benefit analysis in Gajuri Rural Municipality, Dhading. Their findings suggest that dairy farming becomes more profitable when household labor is not monetized and market prices are applied, emphasizing the importance of rural policy support. Acharya and Rajkarnikar assess financial literacy among Nepalese college students, finding that while knowledge of savings and investment is relatively high, financial management understanding remains weak. The study highlights the influence of educational level and digital banking experience on financial literacy. Jnawali and Gyanwaly analyze the impact of foreign aid on Nepal’s economic growth, employing ARDL modeling to show that aid contributes positively to GDP both in the short and long run, particularly when coupled with sound macroeconomic policies and effective aid management. Sachitananda Ghimire provides an ecological and literary critique of Yubaraj Nayaghare’s Ghamko Chumban (Kiss of the Sun). Framed within postmodern and environmental paradigms, the article reveals how the travelogue captures Nepal’s natural, cultural, and linguistic diversity, making it a rich representation of Nepali identity and environmental consciousness. In the field of organizational studies, Kusum K.C. investigates the adoption of HR 5.0 in private organizations in Kathmandu Valley. The study finds that while awareness is high, adoption is hindered by lack of skilled manpower, inadequate digital knowledge, and poor policy support. Strategic planning and government facilitation are recommended to overcome these challenges. Lastly, Ram Chandra Poudel revisits the classical Sanskrit text Bhartrihari’s Shatakatraya, offering biographical insights and critical commentary on the poet’s themes of love, renunciation, and morality. The article blends literary tradition with contemporary relevance, enriching our understanding of ancient wisdom in modern times. Overall, these scholarly articles reflect the journal’s mission to foster critical thinking; encourage empirical and theoretical research; and promote scholarly dialogue across disciplines. This volume showcases how academic inquiry, rooted in the local context, can contribute meaningfully to national discourse and global scholarship. We extend our heartfelt appreciation to the contributing authors, peer reviewers, and editorial team for their dedication and scholarly rigor. We look forward to further engaging with the academic community in our future issues.